Seizure [compact disc, unabridged] - Cook, Robin 1940- (Recorded Books, 2003)
Senator Ashley Butler fervidly opposes any legislation supporting biotechnology and strives to outlaw cloning. His adversary, Dr. Daniel Lowell, has almost perfected an innovative stem cell procedure that reverses the effects of several critical diseases. When Senator Butler learns that he has Parkinson's disease, he puts his political beliefs aside and makes Lowell a surprising offer: he will become Lowell's guinea pig. But when the powerful new technology is unleashed in Butler's brain, the results are devastating.